The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/risks9060120
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Money Laundering Countermeasures: Case Studies from European Union Member States

Abstract: The aim of this study is to present the trends and effectiveness of money laundering countermeasures from the perspective of a number of suspicious transactions reported to the Financial Intelligence Units (FIUs), a number of analysis results submitted to law enforcement authorities, and the typologies of cases in European Union Member States. In order to determine the impact of the joint effort in the fight against money laundering, we used descriptive statistics to process the data and case studies from annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Research has shown that corporate governance and its components have the most significant impact when it comes to reducing the level of fraud, which can be explained by the efficiency of corporate governance mechanisms in reducing the possibility of dishonest financial reporting and ML, which improves the reliability of accounting figures (Razali and Arshad 2014). There are several articles related to suspicious ML transactions (Levi et al 2018;Gilmour 2020;He 2010;Achim et al 2018;Achim et al 2021;Cotoc et al 2021). Today, however, as we face an economic crisis all over the world, this problem needs to be investigated through the lens of corporate governance effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that corporate governance and its components have the most significant impact when it comes to reducing the level of fraud, which can be explained by the efficiency of corporate governance mechanisms in reducing the possibility of dishonest financial reporting and ML, which improves the reliability of accounting figures (Razali and Arshad 2014). There are several articles related to suspicious ML transactions (Levi et al 2018;Gilmour 2020;He 2010;Achim et al 2018;Achim et al 2021;Cotoc et al 2021). Today, however, as we face an economic crisis all over the world, this problem needs to be investigated through the lens of corporate governance effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Lederman (2018), who focuses on tax compliance, also lends support to these studies, reporting evidence of significant impact of enforcement in the case of moderating tax compliance. On the other hand, focusing on the EU Member States, Cotoc et al (2021) emphasizes the need for higher international coordination and cooperation to improve effectiveness of money laundering A major strand of the existing literature focuses on money laundering risk judgment (Trumbo, 1999;Sprinkle, 2003;Arasa, 2015;Parida and Kumar, 2020;Mohd-Sanusi et al, 2021;Jamil et al, 2022), which is somewhat more relevant to the present study. These studies tackle a broad range of issues with respect to money laundering risk.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Lederman (2018), who focuses on tax compliance, also lends support to these studies, reporting evidence of significant impact of enforcement in the case of moderating tax compliance. On the other hand, focusing on the EU Member States, Cotoc et al (2021) emphasizes the need for higher international coordination and cooperation to improve effectiveness of money laundering…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As firms' perceptions of financial crime risk at a jurisdiction level rapidly gain supervisory relevance and international firms continue to reconsider their operations in high-risk jurisdictions, it is imperative to bring empirical evidence to bear on the question of whether political stability, evasion of tax and regulations and regulatory stringency explain firms' perceptions of jurisdiction risks (FCA, 2021a). While different measures of financial crime risk exist, it is notoriously challenging to capture firms' perceptions of it, particularly at a cross-jurisdiction level (Simser, 2013;Cotoc et al, 2021;Perkins, 2022). Financial crime risks can vary significantly across different jurisdictions due to differences in legal and Crossjurisdictional financial crime risks regulatory frameworks, cultural norms and levels of economic development.…”
Section: Introductionmentioning
confidence: 99%